Zinc Biofortification in Food Crops Could Alleviate the Zinc Malnutrition in Human Health - Praharaj, Subhashisa; Skalicky, Milan; Maitra, Sagar; Bhadra, Preetha; Shankar, Tanmoy; Brestic, Marian; Hejnak, Vaclav; Vachova, Pavla; Hossain, Akbar (Molecules (Basel, Switzerland), 2021)
Micronutrient malnutrition is a global health issue and needs immediate attention. Over two billion people across the globe suffer from micronutrient malnutrition. The widespread zinc (Zn) deficiency in soils, poor zinc intake by humans in their diet, low bioavailability, and health consequences has led the research community to think of an economic as well as sustainable strategy for the alleviation of zinc deficiency. Strategies like fortification and diet supplements, though effective, are not economical and most people in low-income countries cannot afford them, and they are the most vulnerable to Zn deficiency. In this regard, the biofortification of staple food crops with Zn has been considered a useful strategy. An agronomic biofortification approach that uses crop fertilization with Zn-based fertilizers at the appropriate time to ensure grain Zn enrichment has been found to be cost-effective, easy to practice, and efficient. Genetic biofortification, though time-consuming, is also highly effective. Moreover, a Zn-rich genotype once developed can also be used for many years without any recurring cost. Hence, both agronomic and genetic biofortification can be a very useful tool in alleviating Zn deficiency.